Deteksi Balantidium sp. pada Babi Domestik (Sus scrofa domesticus) di Desa Jagaraga Kabupaten Lombok Barat - Prisma Regina Dhamayanti; Ni Luh Lasmi Purwanti; Nofisulastri Nofisulastri; Candra Dwi Atma (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Balantidium sp. is a protozoan that can cause balantidiosis, a disease that affects humans and animals. Balantidium coli is part of the normal intestinal flora of domestic and wild pigs. This infection can cause significant economic losses to the pig farming industry, such as livestock mortality, decreased production, and obstacles in the export trade of animal products. This study aims to detect the presence of Balantidium sp. in domestic pigs in Jagaraga Village, Kuripan District, West Lombok Regency. This study is a descriptive study with a cross-sectional design. A total of 30 fresh fecal samples were analyzed using the flotation method and native methods. The results showed 8 positive samples of Balantidium sp., consisting of 6 samples of the cyst stage and 2 samples of the trophozoite stage. Based on the results of the study, it was concluded that pig feces in Jagaraga Village detected Balantidium sp. with cyst and trophozoite stages with a prevalence of 26.6% of 30 samples.